Photodynamic‐Chemodynamic Cascade Reactions for Efficient Drug Delivery and Enhanced Combination Therapy. Issue 10 (8th April 2021) - Wang, Sheng; Yu, Guocan; Yang, Weijing; Wang, Zhantong; Jacobson, Orit; Tian, Rui; Deng, Hongzhang; Lin, Lisen; Chen, Xiaoyuan
Abstract: Nanomedicines with photodynamic therapy and reactive oxygen species (ROS)‐triggered drug release capabilities are promising for cancer therapy. However, most of the nanomedicines based on ROS‐responsive nanocarriers still suffer from serious ROS consumption during the triggered drug release process. Herein, a photodynamic‐chemodynamic cascade strategy for the design of drug delivery nanosystem is proposed. A doxorubicin hydrochloride‐loaded ROS‐responsive polymersome (DOX‐RPS) is prepared via the self‐assembly of amphiphilic poly(ethylene glycol)‐poly(linoleic acid) and poly(ethylene glycol)‐(2‐(1‐hexyloxyethyl)‐2‐devinyl pyropheophorbide‐α)‐iron chelate (PEG‐HPPH‐Fe). The RPS can effectively deliver a drug to tumor site through passive targeting effect. Upon laser irradiation, the photosensitizer HPPH can efficiently generate ROS, which further causes in situ oxidation of linoleic acid chain and subsequent RPS structural destruction, permitting triggered drug release. Intriguingly, catalyzed by HPPH‐Fe, ROS will be regenerated from linoleic acid peroxide through a chemodynamic process. Therefore, ROS‐triggered drug release can be achieved without ROS over‐consumption. The in vitro and in vivo results confirmed ROS generation, triggered drug release behavior, and potent antitumor effect of the DOX‐RPS. This photodynamic‐chemodynamic cascade strategy provides a promising approach for enhanced combination therapy. Abstract : Photodynamic‐chemodynamic cascade strategy: A reactive oxygen species (ROS)‐responsive polymersome is developed for chemo‐photodynamic combination cancer therapy. The ROS generated by photodynamic effect will cause ROS‐triggered drug release. Furthermore, ROS could be regenerated through a Fenton‐like reaction. Therefore, excessive ROS consumption in the drug release process can be avoided.